Identifying factors affecting latent tuberculosis treatment acceptance among healthcare workers: a retrospective analysis in a tertiary care centre - Maskit Bar-Meir; Gali Pariente; Ayal Romem; Yonit Wiener-Well (BMJ Open)
Objective Official guidelines recommend tuberculosis (TB) screening programmes for all healthcare workers (HCWs), along with offering treatment when latent TB infection (LTBI) is diagnosed. However, adherence to treatment among HCWs is lower compared with non-HCWs. The aim of the present study was to examine the rate of LTBI treatment acceptance among HCWs and to characterise the factors associated with non-acceptance.Design and setting This was a retrospective cohort study. All HCWs diagnosed with LTBI, who had tuberculin skin test (TST) conversion during their work, between 2000 and 2015, in a single tertiary academic medical centre, and who consented to answer a questionnaire, were enrolled.Results Overall, 147 of 219 (67%) with TST conversion agreed to participate. Acceptance rate for LTBI treatment was only 16%. The overall completion rate among those who accepted treatment was 87%. HCWs’ recall of discussing the importance of LTBI treatment with their caregiver had the strongest association with LTBI treatment acceptance: 23 of 52 HCWs (44%) who recalled this discussion accepted treatment (adjusted OR=10.2, 95% CI: 2.2 to 47.6, p=0.003). Knowing the risk of developing TB was associated with 3.7 increased odds to accept treatment (95% CI: 1.2 to 11.8, p=0.02).Conclusions LTBI acceptance rate was very low among our HCWs. Focusing on educating HCWs is potentially the key step towards an increased rate of LTBI treatment acceptance.